2018
DOI: 10.3389/fimmu.2018.02319
|View full text |Cite
|
Sign up to set email alerts
|

Class-B CpG-ODN Formulated With a Nanostructure Induces Type I Interferons-Dependent and CD4+ T Cell-Independent CD8+ T-Cell Response Against Unconjugated Protein Antigen

Abstract: There is a need for new vaccine adjuvant strategies that offer both vigorous antibody and T-cell mediated protection to combat difficult intracellular pathogens and cancer. To this aim, we formulated class-B synthetic oligodeoxynucleotide containing unmethylated cytosine-guanine motifs (CpG-ODN) with a nanostructure (Coa-ASC16 or coagel) formed by self-assembly of 6-0-ascorbyl palmitate ester. Our previous results demonstrated that mice immunized with ovalbumin (OVA) and CpG-ODN formulated with Coa-ASC16 (OVA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Along with this, the antigen was formulated with a novel adjuvant strategy, CpG-ODN/Coa-ASC16, that constitutes a nanoplatform. This adjuvant strategy is able to induce potent Th1 and Th17 responses, and elicit long-term antibody responses (27,28). In this study we demonstrated that the immunization of mice with FhKTM/CpG-ODN/Coa-ASC16 increases the survival against F. hepatica challenge.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Along with this, the antigen was formulated with a novel adjuvant strategy, CpG-ODN/Coa-ASC16, that constitutes a nanoplatform. This adjuvant strategy is able to induce potent Th1 and Th17 responses, and elicit long-term antibody responses (27,28). In this study we demonstrated that the immunization of mice with FhKTM/CpG-ODN/Coa-ASC16 increases the survival against F. hepatica challenge.…”
Section: Discussionmentioning
confidence: 70%
“…In this line, the adjuvant capacity of the synthetic oligodeoxynucleotide containing unmethylated cytosine-guanine motifs (CpG-ODN) (agonist of TLR9) formulated with liquid crystal-type nanostructures formed by self-assembly from ascorbyl 6-Opalmitate ester (Coa-ASC16) has been demonstrated. The immunization of mice with the ovalbumin (OVA) protein, together with the adjuvant CpG-ODN/Coa-ASC16, induced a potent antigen-specific antibodies and Th1/Th17/CD8 + T-cell cellular responses without toxic systemic effects (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…The OVA-specific antibody titers were measured by ELISA as described by Chiodetti et al 18 Titer was considered to be the reciprocal of the last serum dilution that yielded an absorbance value 490 nm greater than that of twice the mean value of blank. The sera from nonimmunized mice were not reactive to OVA.…”
Section: Ova-specific Igg1 and Igg2a Titersmentioning
confidence: 99%
“…CpG is an adjuvant composed of multiple synthetic oligodeoxynucleotides (rich in unmethylated cytosine-guanine motifs) with the capacity to induce expression of proinflammatory cytokines and costimulatory molecules in multiple cells, including dendritic cells (DCs), macrophages, and total leukocytes (31)(32)(33). CpG-adjuvanted vaccines generate long-lasting antibody responses as well as CD4 + and CD8 + T-cell responses against co-immunized antigens like OVA (34). Importantly, CpG promotes type-I interferon release and Th1 responses against different coadministered antigens, both of which are important in generating effective antiviral responses (35,36).…”
Section: Introductionmentioning
confidence: 99%